Indonesia Languange Utterance by Nias People in Gunung Sitoli - Amelia Yuli Astuti; Silvia Ningsih Zebua (Jurnal Ilmiah Langue and Parole, 2021)
This research aims to find out the factors that influence the pronunciation of Nias people when using Indonesian as a second language, to find out the rules of language change. The theory used in this research is the theory of behaviorism and neutral theory. This research used qualitative research methods and observation techniques to collect data. Data were taken based on interviews with respondents, video recordings of interviews and field notes found in the form of words. The collected data were analyzed using inductive methods and using error analysis techniques to analyze research data. This research interviewed forty five years old man and forty two years woman who are living in Gunung Sitoli. The data collected is related to basic swadesh vocabulary and vocabulary that is not included in swadesh which changes when spoken into Indonesian. The results of the collected data describe and represent the wrong pronunciation when pronouncing Indonesian. The results of this research indicate four factors that influence the change in Nias language in Indonesian. These factors occur because of the differences in the language system of Nias and Indonesian. The use of the Nias language is more dominant than the Indonesian language, the Nias people always use the regional language (Nias) in a formal atmosphere.